Dispositional Factors in Internet Use: Personality Versus Cognitive Style1 - McElroy, James C.; Hendrickson, Anthony R.; Townsend, Anthony M.; DeMarie, Samuel M. (MIS Quarterly, 2007)
This study directly tests the effect of personality and cognitive style on three measures of Internet use. The results support the use of personality—but not cognitive style—as an antecedent variable. After controlling for computer anxiety, self-efficacy, and gender, including the “Big Five” personality factors in the analysis significantly adds to the predictive capabilities of the dependent variables. Including cognitive style does not. The results are discussed in terms of the role of personality and cognitive style in models of technology adoption and use.